RCWS Control System Design Based on Raspberry Pi - Danu, Aswin; Maajid, Lukman; Kasiyanto, Kasiyanto (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2021)
The Raspberry Pi was used in Control system projects, this project is intended to realize a system, i.e., the Raspberry Pi-based RCWS control system, where the RCWS movement uses a DC motor therefore, that it will make it easier for shooters to reach their targets.Thus, the shooter can determine the position of the weapon that will be used at a distance from the shooter's position by using the smartphone screen to monitor the target or target to be shot. The test results show that [1] Raspberry Pi can be used to control RCWS to move towards elevation and azimuth angles when determining the target determined via a web browser, where the voltage generated by the GPIO pin is in a low condition of 0.5mV whilein high conditions it is equal to 3,282V.